A Resource Scheduling Strategy in Cloud Computing Based on Multi-agent Genetic Algorithm - Wuxue Jiang; Jing Zhang; Junhuai Li; Hui Hu (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Resource scheduling strategies in cloud computing are used either to improve system operating efficiency, or to improve user satisfaction. This paper presents an integrated scheduling strategy considering both resources credibility and user satisfaction. It takes user satisfaction as objective function and resources credibility as a part of the user satisfaction, and realizes optimal scheduling by using genetic algorithm. We integrate this scheduling strategy into Agent subsequently and propose a cloud computing system architecture based on Multi-agent. The numerical results show that this scheduling strategy improves not only the system operating efficiency, but also the user satisfaction. DOI: http://dx.doi.org/10.11591/telkomnika.v11i11.3497